An Overview of knowledge level of adolescent girls about anemia disease and prevention in Badung area, Bali - Sari, Gusti Ayu Putu Laksmi Puspa; Wibowo, Yosi Irawati; Yana, I Gusti Agung Ari Kusuma; Megawati, Fitria (Pharmaceutical Journal of Indonesia, 2025)
Introduction: Adolescent anemia in Indonesia is still a high health problem, despite the implementation of government programs related to adolescent anemia prevention. Knowledge is one of the factors and influences the success of anemia prevention programs in adolescents. Objective: To provide an overview of knowledge related to blood supplement tablets and anemia in adolescent girls in Badung area. Methods: A survey study using a questionnaire was conducted on 193 adolescent girls enrolled in one of the junior high schools in Badung. There were twenty knowledge questions related to blood supplement tablets and anemia. Data were analyzed descriptively based on the variables measured. Results: The knowledge level of adolescent girls mostly had sufficient knowledge (74.6%), good knowledge (11.9%) and poor knowledge (13.5%). Conclusion: In this study, there were still adolescent girls who had insufficient knowledge. Educational efforts need to be made in various approaches to improve the knowledge of adolescent girls.